2018
DOI: 10.3390/en11020338
|View full text |Cite
|
Sign up to set email alerts
|

Device Performance Improvement of Recycling Double-Pass Cross-Corrugated Solar Air Collectors

Abstract: Abstract:The device performance of cross-corrugated double-pass solar air heaters under external recycle conditions was investigated experimentally and theoretically, and solved numerically using the Newton method. Comparisons were made and represented graphically among three different configurations of the single-pass, flat-plate double-pass and cross-corrugated double-pass devices. Air flowing simultaneously over the wavelike corrugated absorbing plate and in-between both wavelike cross-corrugated absorbing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The recycle ratio of 1.8 yielded the largest thermohydraulic efficiency. Ho et al [13] utilized corrugated absorber and back plates to improve heat transfer in a double-pass SAH with recycled flow. It was shown that the thermal performance improved with an increasing recycle ratio and decreasing air flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…The recycle ratio of 1.8 yielded the largest thermohydraulic efficiency. Ho et al [13] utilized corrugated absorber and back plates to improve heat transfer in a double-pass SAH with recycled flow. It was shown that the thermal performance improved with an increasing recycle ratio and decreasing air flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the present study is to develop the optimal design experimentally and theoretically and identify the best operational conditions such as the recycle ratio and air mass flow rate. The corrugated absorber configurations investigated in our previous study [33] showed that a significant enhancement of the thermal performance of solar air collectors was achieved. This motivated us to introduce various external-recycle operations to resolve the disadvantages of remixing effects and preserve the advantages of convective turbulent flows in the conventional flat-plate solar air heater upgraded through examining various configurations and operating conditions.…”
Section: Introductionmentioning
confidence: 92%
“…At this time, n, which is represented by a slope, is 0.6828. Therefore, Equation (16) can be written as Equation (18). At this time, n, which is represented by a slope, is 0.6828.…”
Section: Correlations For Nusselt Number (Nu) and Friction Factor (F)mentioning
confidence: 99%
“…At this time, n, which is represented by a slope, is 0.6828. Therefore, Equation (16) can be written as Equation (18).…”
Section: Correlations For Nusselt Number (Nu) and Friction Factor (F)mentioning
confidence: 99%
See 1 more Smart Citation